(untitled) (Nexo Revista Científica, 2023)
This paper examines the influence of recreational activities on the components of coastal landscapes on the territory of the municipal formation of the resort city of Gelendzhik, Russia (the Betta farm). The authors provide an estimation of the anthropogenic impact on the soils. The paramagnetic activity of meadow-chernozem soils is studied using electron paramagnetic resonance spectroscopy. The authors also review other aspects related to soil changes. Finally, conclusions are drawn about the progress of the study, and appropriate recommendations are given.